Educational program for coronary artery disease patients: results after one year - Eliana de Cássia Arantes; Carina Aparecida Marosti Dessotte; Rosana Aparecida Spadoti Dantas; Lidia Aparecida Rossi; Rejane Kiyomi Furuya
ASTRACT Objective: To evaluate the long-term results of an educational program compared to usual care. Method: A longitudinal study in which 56 participants from a previous study (randomized controlled clinical trial) were evaluated twelve months after the percutaneous coronary intervention (PCI). Health-related quality of life (HRQoL) was assessed by the Medical Outcomes Study: 36-item Short Form (SF-36), and anxiety and depression symptoms were assessed by the Hospital Anxiety and Depression Scale (HADS). A repeated measures analysis of variance was performed (significance level 0.05). Results: Participants in the educational program showed improvement of HRQoL in the Role-Emotional domain, while those in the usual care did not present changes (p=0.05). Both groups showed improvement in the Role-Physical (p = 0.001) and Bodily Pain (p=0.01) domains over time. There were no differences in the symptoms of anxiety and depression. Conclusion: One year after the PCI, there were significant differences between groups only for the Role-Emotional domain of the SF-36.